Education Investment Guide : A Guide for Investors in Private Education in Emerging Markets - International Finance Corporation (World Bank, Washington, DC, 2014)
This guide has been prepared as a reference for International Finance Corporation (IFC) partner banks and other investors considering an investment in private education. It aims to: 1) describe some of the special features of private education entities, such as primary and secondary schools, technical and vocational colleges as well as tertiary colleges and universities; and 2) indicate the key questions to ask and what to look for when such institutions are being appraised. The document is divided into four sections: i) the education sector in emerging economies; ii) investing in education; iii) national policies and regulation; and iv) good practice, pitfalls and performance. The first section sets the education market in a global context, explaining why the private sector is emerging as a major player in many countries. The second section sets out the different approaches of private equity and banks as lenders. The next section focuses on the national context and describes some of the national policies and regulations that might influence the operations and profitability of an education institution. The final section illustrates the elements of a successful education investment from both the financial and educational points of view.